Effectiveness of Using E-Wallet as an Alternative to Payment of Parking Fees in Mataram City - Ihza Fitriani; Herlina Pusparini (PT FORMOSA CENDEKIA GLOBAL, 2024)
Public service levies are one of the largest contributors to PAD through Parking Levy. However, the lack of optimal handling has resulted in regional levies still being the lowest figure in the row of types of Regional Original Income. The Mataram City Government has made a breakthrough with regulations using E-Wallet as a means of paying parking fees. This research seeks to see whether the use of E-Wallet is effective for paying parking fees. Using quantitative methods, data collected through the Financial Report of the Mataram City Transportation Department for 2021 to 2023 is continuously processed using effectiveness ratios. The results show that the use of E-Wallet as a means of paying parking fees based on revenue targets and revenue realization for 3 (three) years from 2021 to 2023 at the Mataram City Transportation Service using an effectiveness ratio gets an average result of 43.45%, which is included in the category ineffective. However, using E-Wallet to pay parking fees is very easy and fast, there is no change and receiving money directly makes transactions safer and also improves parking collection services in Mataram City, minimizing the occurrence of illegal collections carried out by irresponsible individuals. responsibility, and provide satisfaction and transparency of payments in accordance with government regulations to parking service users.